Pendidikan Kesehatan Tentang Menstruasi Dan Permasalahannya Sebagai Upaya Meningkatkan Pengetahuan Remaja Mengenai Kesehatan Reproduksi Di SMK Hijau Muda Cikarang Utara - Ade Krisna Ginting; Ikha Prastiwi; Marini Iskandar; Zuriati; Yola Masofa; Devi Arianti; Eka Apriani; Nurva Diana (Jurnal Pengabdian kepada Masyarakat Cahaya Negeriku, 2021)
Background: According to the World Health Organization (WHO) in 2018 the incidence of dysmenorrhea in the world is very large, on average more than 50% of women in every country experience dysmenorrhea. Results Based on a preliminary study conducted at SMA Negeri 2 Cikarang Utara with the number of respondents as many as 10 students who were interviewed, it was found that 70% (7 students) had dysmenorrhea, and only 30% (3 students) did not experience dysmenorrhea. In addition, there is still a low knowledge of adolescents about dysmenorrhea as much as 32.9% (51 people) and 51% (79 people) of adolescents about handling dysmenorrhea. Purpose: Efforts to increase knowledge about menstrual problems and how to handle menstrual problems. Method: Distribution of leaflets and explanations about menstrual problems and how to handle them at SMK Hijau Muda Cikarang Utara class X and XII.Results: Based on the 40 targets, the knowledge level of adolescents increased to 95% (38 people) having knowledge in the very good category and 5% (2 people) having knowledge in the good category.. Conclusion: The youth of SMK Hijau Muda Cikarang Utara have understood and understood the problems related to menstruation and how to handle them